2016
DOI: 10.18632/oncotarget.11683
|View full text |Cite
|
Sign up to set email alerts
|

TNFSF15 suppresses VEGF production in endothelial cells by stimulating miR-29b expressionviaactivation of JNK-GATA3 signals

Abstract: Vascular endothelial cell growth factor (VEGF) plays a pivotal role in promoting neovascularization. VEGF gene expression in vascular endothelial cells in normal tissues is maintained at low levels but becomes highly up-regulated in a variety of disease settings including cancers. Tumor necrosis factor superfamily 15 (TNFSF15; VEGI; TL1A) is an anti-angiogenic cytokine prominently produced by endothelial cells in a normal vasculature. We report here that VEGF production in mouse endothelial cell line bEnd.3 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The VEGI174 protein and its domain peptides (V7 and V8) exhibited inhibitory effects on RCC proliferation, migration and invasion; however, the exact mechanism remains unclear. Zhang et al (38) reported that VEGF expression could be suppressed by VEGI-stimulated TNF superfamily member 15 activation of the Jun N-terminal kinase-GATA binding protein 3 signalling pathway. Qi et al (39) reported that VEGI inhibits vasculogenesis by regulating the relative levels of membrane-bound and soluble isoforms of VEGF receptor-1.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGI174 protein and its domain peptides (V7 and V8) exhibited inhibitory effects on RCC proliferation, migration and invasion; however, the exact mechanism remains unclear. Zhang et al (38) reported that VEGF expression could be suppressed by VEGI-stimulated TNF superfamily member 15 activation of the Jun N-terminal kinase-GATA binding protein 3 signalling pathway. Qi et al (39) reported that VEGI inhibits vasculogenesis by regulating the relative levels of membrane-bound and soluble isoforms of VEGF receptor-1.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of VEGF that was detected by IHC was significantly decreased in the VEGI174-treated group compared to the saline-treated group. Zhang et al reported that VEGF gene expression could be suppressed by TNFSF15 (VEGI)-stimulated activation of the Jun N-terminal kinase-GATA binding protein 3 (JNK-GATA3) signaling pathway (26). Qi et al found that VEGI inhibited vasculogenesis by regulating relative levels of membrane-bound and soluble isoforms of VEGF receptor 1 (23).…”
Section: Discussionmentioning
confidence: 99%
“…We established an intracranial hemangioma model by injecting bEnd.3 cells into the right basal ganglia. The bEnd.3 cells, which exhibit low TNFSF15 and high VEGF expression levels (9,24), formed highly vascularized and extensively hemorrhagic vascular lesions in the 7 d following injection ( Fig. 2A).…”
Section: Engineered Overexpression Of Tnfsf15 In Bend3 Cells Leads Tmentioning
confidence: 99%
“…TNFSF15 has been shown to be able to inhibit VEGF/VEGF receptor (VEGFR) 1-mediated, EPC-supported vasculogenesis (22) and to induce dephosphorylation of VEGFR2, thus blocking VEGF-induced, VEGFR2-mediated vascular hyperpermeability (23). Additionally, TNFSF15 suppresses VEGF production in endothelial cells by stimulating microRNA (miR)-29b expression (24,25), whereas VEGF suppresses TNFSF15 production in endothelial cells by stimulating miR-31 and miR-20a expression (24,25). Such a counterbalance of pro-and antiangiogenesis systems may be of significance in the maintenance of vascular homeostasis under physiologic conditions as well as the modulation of angiogenic microenvironment under pathologic conditions.…”
mentioning
confidence: 99%